Ignacio Álvarez Borge, La plena Edad Media. Siglos XII-XIII - Paola Jiménez Álvarez (Medievalia)
Ignacio Álvarez Borge, La plena Edad Media. Siglos XII-XIII, Madrid: Síntesis, 2003 (Historia de España 3er. Milenio, 8).